Complementarity of Technology Adoption and Social Capital Participation: The Case of Systems of Rice Intensification in Ghana. (1st July 2019) - Yahaya, Iddrisu; Zereyesus, Yacob A.; Nakelse, Tebila; Haruna, Bashiru
Abstract: Rice is the second most important staple food in Ghana. The system of rice intensification (SRI) technology has been introduced in farmers' fields, and its adoption is increasing. Using a bivariate probit model and maximum likelihood estimation methods, the study tests whether or not there is a complementarity relationship between adoption of SRI technology and membership in a cooperative. Results reveal that there is positive relationship between the SRI adoption and social capital participation. The study identified covariates including age, gender and educational level of respondents as influencing both the adoption of SRI technology and participation in a cooperative. © 2019 John Wiley & Sons, Ltd.